ANALISA EFISIENSI KOLEKTOR SURYA PLAT DATAR DENGAN DEBIT ALIRAN FLUIDA 3-10 LITER/MENIT - Sulaeman; Darul Mapasid (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2013)
Solar thermal energy is one of the potential energy to be explored and developed further as a source of backup energy. To be able to directly utilize solar thermal energy to heat water can be used in a device that can collect solar energy to the Earth's surface and convert it back into useful heat energy. This device is called the solar collector. Solar collectors can be defined as a heat transfer system that generates thermal energy by harnessing the Sun's radiation as the main source of energy. After testing by varying the flow capacity of 3 litters /minute up to 10 liters/minute, then in the temperature of the fluid can come out (Tout) is the highest of 61,9 C, which is present on the stream discharge 7,5 litters/minute. And the highest efficiency in the discharge flow of 5 litters /minute is equal to 86,54%. The results of this test indicate the efficiency of the collector surya.